Obesity Causes Abrupt Changes in the Testicular Microbiota and Sperm Motility of Zebrafish - Su, Yufang; He, Liting; Hu, Zhiyong; Li, Ying; Zhang, Yuan; Fan, Zunpan; Zhao, Kai; Zhang, Huiping; Liu, Chunyan (Frontiers in Immunology, 2021)
Background Obesity is a recognized risk factor for low fertility and is becoming increasingly prevalent in many countries around the world. Obesity changes intestinal microbiota composition, causes inflammation of various organs, and also reduces sperm quality. Several microorganisms are present in the testis. However, whether obesity affects the changes of testicular microbiota and whether these changes are related to reduced fertility in obese men remain to be elucidated. Methods In the present study, a zebrafish obesity model was established by feeding with egg yolk powder. Sperm motility was measured by the Computer Assisted Sperm Analysis system, testicular microbial communities was assessed via 16s RNA sequencing, the immune response in zebrafish testis was quantified by quantitative real-time polymerase chain reaction and enzyme-linked immunosorbent assay, and the testicular tissue structure was detected by electron microscopy and hematoxylin–eosin staining. Results Compared with the control group, zebrafish sperm motility was dramatically reduced, the expression of testicular proinflammatory cytokines in the testes was upregulated, and the blood–testis barrier structure was disrupted in the obese group. In addition, testicular microbiome composition was clearly altered in the obese group. Conclusion Obesity alters testicular microbiota composition, and the reason behind the decreased sperm motility in obese zebrafish may be related to changes in the testicular microbial communities.